Nanoscale geometry determines mechanical biocompatibility of vertically aligned nanofibers - Rantataro Samuel; Parkkinen Ilmari; Pandea Ishan; Domanskyi Andrii; Airavaara Mikko; Peltola Emilia; Laurila Tomi (Elsevier, 2022)
Vertically aligned carbon nanofibers (VACNFs) are promising material candidates for neural biosensors due to their ability to detect neurotransmitters in physiological concentrations. However, the expected high rigidity of CNFs could induce mechanical mismatch with the brain tissue, eliciting formation of a glial scar around the electrode and thus loss of functionality. We have evaluated mechanical biocompatibility of VACNFs by growing nickel-catalyzed carbon nanofibers of different lengths and inter-fiber distances. Long nanofibers with large inter-fiber distance prevented maturation of focal adhesions, thus constraining cells from obtaining a highly spread morphology that is observed when astrocytes are being contacted with stiff materials commonly used in neural implants. A silicon nanopillar array with 500 nm inter-pillar distance was used to reveal that this inhibition of focal adhesion maturation occurs due to the surface nanoscale geometry, more precisely the inter-fiber distance. Live cell atomic force microscopy was used to confirm astrocytes being significantly softer on the long Ni-CNFs compared to other surfaces, including a soft gelatin hydrogel. We also observed hippocampal neurons to mature and form synaptic contacts when being cultured on both long and short carbon nanofibers, without having to use any adhesive proteins or a glial monoculture, indicating high cytocompatibility of the material also with neuronal population. In contrast, neurons cultured on a planar tetrahedral amorphous carbon sample showed immature neurites and indications of early-stage apoptosis. Our results demonstrate that mechanical biocompatibility of biomaterials is greatly affected by their nanoscale surface geometry, which provides means for controlling how the materials and their mechanical properties are perceived by the cells.